The Role of Service Quality in Building Customer Satisfaction: A Literarure Review - Elia Cahyani; Tazkiyyah Nururrohmah; Cindy Firstiananda Deka; Mohamad Zein Saleh (Universitas 45 Surabaya, 2024)
The role of service quality in the service business is very important to improve customer satisfaction. Service management focuses on providing services that not only meet but also exceed customer expectations, creating a significant competitive advantage. Service quality serves as a bridge between the company and customers, establishing a long-term, mutually beneficial relationship. In the era of globalization and digitalization, customer interactions that take place mostly online demand companies to offer responsive and efficient digital experiences. Consistency in service delivery is a major challenge, as customers assess the quality of service based on their subjective experience. This study aims to review the literature related to the role of service quality in building customer satisfaction, the factors that affect it, and how companies can implement good service quality to improve customer satisfaction.